THE PERFORMANCE OF RURAL DEVELOPMENT SCHEME IN ISLAMI BANK BANGLADESH FROM AN ISLAMIC PERSPECTIVE - Mohammad Saiful Islam (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2016)
Islami Bank Bangladesh Limited (IBBL) is one of the leading and efficient financial institutions in the globe. The Rural Development Scheme (RDS) has become an exclusive domain to play a significant role in increasing the performance of development in nation building. As a result, IBBL is playing a vital role in the rural area in applying the RDS for poverty alleviation. The aim of this study is to analyze the performance of the RDS of IBBL in the rural area. This paper will also discuss the achievements of this scheme in the present context to evaluate its performance. Finally, the researcher will come up with some suggestions and recommendations for further improvement. =========================================== Bank Islami Bangladesh Limited (IBBL) adalah salah satu lembaga keuangan terkemuka dan efisien di dunia. â€œSkema Pembangunan Pedesaanâ€ (RDS) telah menjadi suatu domain yang ekslusif dalam memainkan peranan yang signifikan bagi peningkatan performa dalam pembangunan negara. Sebagai hasilnya, IBBL memainkan peranan yang penting di daerah pedesaan dalam mengaplikasikan skama RDS bagi upaya penanggulangan kemiskinan. Tujuan penelitian ini adalah untuk menganalisa performa skema RDS dari IBBL di daerah pedesaan. Paper ini juga akan mendiskusikan pencapaian skaema ini dalam konteks saat ini guna mengevaluasi performanya. Pada akhirnya, peneliti akan menyampaikan beberapa saran dan rekomendasi untuk peningkatan di masa yang akan datang.